2014
DOI: 10.3346/jkms.2014.29.7.985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Epidemiology, Emergency Care, and Outcomes of Acute Ischemic Stroke between Young Adults and Elderly in Korean Population: A Multicenter Observational Study

Abstract: Stroke in young adults has been known to show a lower incidence and a better prognosis. Only a few studies have examined the epidemiology and outcomes of ischemic stroke in young adults and compared them with the elderly in Korean population. All consecutive patients with ischemic stroke visiting 29 participating emergency departments were enrolled from November 2007 to October 2009. Patients with less than 15 yr of age and unknown information on age and confirmed diagnosis were excluded. We categorized the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…In this study the majority of patients at the time of admission showed a moderate stroke severity according to the NIHSS, which is in consonance with Rena et al 9 2014, a study conducted on a stroke unit in Italy, which evaluated 150 patients young adults. When compared the types of stroke, the greater frequency of ischemic stroke in this study corroborates to what has been described in the literature 3,4,18,19,22 , in particular, the proportion of patients diagnosed with hemorrhagic stroke were mostly of hypertensive etiology, reasoning with the findings of previous studies 3,4 . There was a statistically significant difference when comparing female and male with hypertensive etiology of hemorrhagic stroke: the most hypertensive were men, presenting higher frequency of hemorrhagic stroke.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…In this study the majority of patients at the time of admission showed a moderate stroke severity according to the NIHSS, which is in consonance with Rena et al 9 2014, a study conducted on a stroke unit in Italy, which evaluated 150 patients young adults. When compared the types of stroke, the greater frequency of ischemic stroke in this study corroborates to what has been described in the literature 3,4,18,19,22 , in particular, the proportion of patients diagnosed with hemorrhagic stroke were mostly of hypertensive etiology, reasoning with the findings of previous studies 3,4 . There was a statistically significant difference when comparing female and male with hypertensive etiology of hemorrhagic stroke: the most hypertensive were men, presenting higher frequency of hemorrhagic stroke.…”
supporting
confidence: 82%
“…Most of the population of this study was in full socioeconomic activity, corroborating the studies of Park et al 19 , 2014, conducted by 29 Korea Information emergency system with 1,431 young adults which identified 74% of individuals evaluated in work activity. Stroke is a disabling disease 7 and the involvement of this active population will bring losses to social security, reaching a rate of 40% of early retirement 8 with a range of 40 to 93% of patients not returning to previous activity, requiring permanent removal from professional activities 11.27 28 .…”
supporting
confidence: 78%
See 1 more Smart Citation
“…18,19 Previous Korean studies had a male preponderance, as in our study. 20,21 Higher prevalence rates of hypertension and smoking and a higher BMI in males seem to be the reasons for this difference. A previous multicenter study of IS in young Korean adults (aged between 15 and 45 years) from 2007 to 2010 found hypertension in 18.0%, DM in 7.8%, and dyslipidemia in 2.6% of the enrolled patients.…”
Section: Jcnmentioning
confidence: 99%
“…According to Table 1, one could deduce that the highest group was the retired and the employees. In Korea, the respondents were catagorized into two groups , education and occupation [22][23][24] . Similarly in Indonesia, stroke is common among low and middle class.…”
Section: Occupationmentioning
confidence: 99%